Engagement of membrane immunoglobulin enhances Id3 promoter activity in WEHI-231 B lymphoma cells - LI Xiao-jun; HATA Kikumi; MIZUGUCHI Junichiro (Acta Pharmacologica Sinica, 2016)
Aim: We have recently shown that engagement of membrane immunoglobulin (mIg) induced upregulation of inhibitor of differentiation 3 (Id3) mRNA, resulting in growth arrest at G1 phase in WEHI-231 cells. In the present study, we examined whether engagement of mIg will affect promoter activity of the Id3 gene in WEHI- 231 cells. Methods: DNA fragments corresponding to the 5'-flanking region of mId3 gene were amplified by polymerase chain reaction (PCR) using genomic DNA as the template. Three DNA fragments upstream of the transcription start site (+1) of the mId3 gene were subcloned into the luciferase reporter vector PGVB2. The recombinant constructs were transiently transfected into WEHI-231 cells by an electroporation method. After incubation for 24 h, WEHI-231 cells were stimulated with 10 mg/L anti-IgM or irradiated CD40L-expressing NIH3T3 cells or control NIH3T3 cells for further 24 h, followed by assay for luciferase activity. Results: The luciferase analysis demonstrated that basal promoter activity of the Id3 gene was found in the region between -200 and +54. The Id3 promoter activity was increased 2-fold following stimulation with anti-IgM, but not CD40L, compared with medium alone. Conclusion: The mIg-mediated upregulation of Id3 expression is controlled, at least in part, through transcriptional regulation, as assessed by luciferase assay.